THE READING COMPREHENSION OF TEXT WITH DIFFERENT LEXICAL DENSITY AND TOPIC FAMILIARITY OF GRADE TEN STUDENTS OF SMA SW KATOLIK BUDI MURNI 2 MEDAN. - Laura Esterlita br Sinuhaji; Prof. Dr. Berlin Sibarani, M.Pd; Tiarnita Maria Sarjani Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2024)
This study aims with reading comprehension of grade ten students of SMA SW Katolik Budi Murni 2 Medan. The objective of this study is(1) describe the students reading comprehension across text of different lexical density and topic familiarity and (2) to find out the effect of lexical density and topic familiarity in reading comprehension. The research was conducted bydescriptive qualitative with non-parametric statistic research. The research was conducted in SMA SW Katolik Budi Murni 2 Medan at the grade ten classroom. the sample of the research were 10 students. The instruments for collecting data used in this research were six reading text with different lexical density and topic familiarity and of reading comprehension test.The result of the analysis showed that: (1) Familiar text is easier to comprehend for the students than the unfamiliar text when they both have low lexical density, while familiar text with medium and high lexical density is the same difficult for the students to comprehend as the unfamiliar text. (2) Text with low lexical density is easier for the students to comprehend than text with medium and high lexical density when the texts are both familiar. While texts with low and medium lexical density is the same difficult for the students to comprehend as the text with high lexical density when the text are unfamiliar.